2018
DOI: 10.2147/jep.s180777
|View full text |Cite
|
Sign up to set email alerts
|

In vitro pharmacological characterization of SPN-810M (molindone)

Abstract: BackgroundImpulsive aggression (IA) is considered a maladaptive form of aggression that is reactive and overt and occurs outside of the acceptable social context. Many children and adolescents with attention-deficit/hyperactivity disorder (ADHD) display clinically significant aggression, with the predominant subtype being IA. However, there is currently no Food and Drug Administration-approved medication specifically to treat IA. The pathophysiology of IA is not fully understood, although it has been suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Even molindone, while considered an older antipsychotic, has serotonin blocking actions similar to the new atypical antipsychotics. 28 As is true of brexpiprazole, many newer drugs that are effective in treating psychosis have effects that go far beyond blockade of the DA 2 receptor, which may explain the use of these drugs in ADHD. Brexpiprazole has partial agonist activity at the DA 2 receptor, plus actions at several serotonergic receptors as well as α noradrenergic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even molindone, while considered an older antipsychotic, has serotonin blocking actions similar to the new atypical antipsychotics. 28 As is true of brexpiprazole, many newer drugs that are effective in treating psychosis have effects that go far beyond blockade of the DA 2 receptor, which may explain the use of these drugs in ADHD. Brexpiprazole has partial agonist activity at the DA 2 receptor, plus actions at several serotonergic receptors as well as α noradrenergic.…”
Section: Discussionmentioning
confidence: 99%
“…All of the antipsychotic medications mentioned in the Introduction, which have been used with a stimulant, with the exception of molindone, are considered atypical antipsychotics with much more diverse neurochemical actions. Even molindone, while considered an older antipsychotic, has serotonin blocking actions similar to the new atypical antipsychotics 28 . As is true of brexpiprazole, many newer drugs that are effective in treating psychosis have effects that go far beyond blockade of the DA 2 receptor, which may explain the use of these drugs in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact mechanism of SPN-810 is unknown, emerging data suggest it functions as an antagonist of the dopamine receptors D 2S and D 2L and the serotonin receptor 5-HT 2B [90]. Although it remains to be confirmed, given these activities and the purported neuropathology of IA, it is suggested that SPN-810 may function by modulating the dopamine limbic pathway and its associated neural networks [15,90,91]. Further, the reduced incidence of EPS at therapeutic doses used for IA suggests that the potency of SPN-810 achieved at low doses is different from that of doses used for schizophrenia, which are highly associated with EPS [92].…”
Section: A Case Example Of An Ia Modulatormentioning
confidence: 99%
“…In addition, its use is also considered in ADHD therapy (attention-deficit/hyperactivity disorder) [1][2][3]. The mechanism of molindone action assumes D 2S , D 2L , D 5 dopamine, and 5-HT 2B serotonin receptor antagonist activity and remains strictly in correlation with the dopamine hypothesis of schizophrenia [4][5][6][7][8][9]. It should also be noted that patients treated with molindone are exposed to the occurrence of side effects, for instance, tardive dyskinesia or akathisia, according to the commonly known mechanism of neuroleptics dopamine antagonistic potential [10][11][12].…”
Section: Introductionmentioning
confidence: 99%